Antibacterial Activity Test of Ethanol Extract Citrus Leaf Against Staphylococcus epidermidis - Anindita, Reza; Sulvayanti, Hana Yelsi; Inggraini, Maulin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
One of the causes of acne is an increase in colonies of Staphylococcus epidermidis bacteria. One of the acne treatments that trigger bacterial resistance is the irrational use of antibiotics. Therefore, it is necessary to discover natural materials with antibacterial potential, namely orange plants. This study aims to determine the effect of single and combination of lime, kaff, lemon, and sweet leaves extract on of S. epidermidis. The treatment of this study was the concentration of orange leaf ethanol extract of 2%, 4%, and 8% with a bacteria sample of S. epidermidis. Phytochemical screening test results contain alkaloids, flavonoids, saponins, tannins, phenols, and essential oils. The results of the One-Way ANNOVA test showed a significant difference in the average diameter of the inhibition zone of orange leaf ethanol extract against the growth of S. epidermidis (Sig.<0.05). Post Hoc test showed that the effective concentration of lime leaves, kaffles, lemons, sweet oranges, and combination was 8%, while sweet oranges are the most significant treatment group in inhibiting the growth of S. epidermidis. The conclusion is that 8% sweet lime leaf ethanol extract can be used as a pharmaceutical raw material in inhibiting the growth of S. epidermidis with a strong category.